EFEKTIVITAS INSEKTISIDA NABATI DALAM MENGENDALIKAN HAMA KUTU PUTIH (Paracoccus marginatus) PADA TANAMAN PEPAYA (Carica papaya L.) - Muhamad Rizal; Seprita Lidar; Roy Ibrahim (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2023)
Papaya (Carica papaya L.) cultivation gets a lot of disturbances such as pests or diseases that can reduce the quality and quantity of papaya fruit. The use of vegetable insecticides is effective in controlling pests and has potential as a plant insecticide such as citronella, neem and cloves. This study aims to determine daily mortality and obtain the most effective botanical insecticides in controlling mealybug pests on papaya plants. The study consisted of two stages: (1) assessing the percentage of daily mortality, (2) the effectiveness of citronella oil, neem extract and clove oil vegetable insecticides on papaya seedlings. Daily mortality data were calculated using the daily mortality formula and data on the effectiveness of vegetable insecticides were analyzed using analysis of variance. The results showed that the highest percentage of mortality by giving citronella oil had a 24-hour daily mortality percentage and clove oil at a 48-hour daily mortality percentage. Botanical insecticides had an effect on all observation parameters, plant height, number of leaves and stem diameter, while the most effective treatment in controlling the mealybug P. marginatus treatment N1 was citronella oil with a concentration of 1 cc/500 mL.